2020
DOI: 10.1016/j.envres.2020.109650
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollutants on the transmission and severity of respiratory viral infections

Abstract: Particulate matter, sulfur dioxide, nitrogen oxides, ozone, carbon monoxide, volatile organic compounds (VOCs) and polycyclic aromatic hydrocarbons (PAHs) are among the outdoor air pollutants that are major factors in diseases, causing especially adverse respiratory effects in humans. On the other hand, the role of respiratory viruses in the pathogenesis of severe respiratory infections is an issue of great importance. The present literature review was aimed at assessing the potential effects of air pollutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
223
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(254 citation statements)
references
References 77 publications
7
223
1
10
Order By: Relevance
“…Air pollution has been reported to increase the risk of SARS-CoV-2 infection [11,12]. ACE2 is considered to play an important role in regulation of SARS-CoV-2 infection ability [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air pollution has been reported to increase the risk of SARS-CoV-2 infection [11,12]. ACE2 is considered to play an important role in regulation of SARS-CoV-2 infection ability [18].…”
Section: Discussionmentioning
confidence: 99%
“…COPD is known to cause deficits in ACE2 in the lungs [9,10]. Air pollution is a risk factor for the development of COPD, which is also suspected to be associated with the SARS-CoV-2 infection ability [11,12]. The objective of this study was to investigate the expressions of ACE2 by air pollution during the development of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Though there is some evidence that air pollution may enhance the susceptibility to viral infections including that by SARS-CoV-2 (Barcelo, 2020;Chen et al, 2010;Domingo and Rovira, 2020;Peng et al, 2020;Tsatsakis et al, 2020), the connection is still speculative. Transmission of airborne infections such as that due to SARS-CoV-2 occurs mainly through droplets and aerosols in the vicinity of infected individuals (Gabutti et al, 2020), but airborne particles might serve as carriers for pathogens (Setti et al, 2020a;SIMA, 2020;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has established associations between exposure to air pollution and spread of measles 14,15 and spread of respiratory diseases 16,17 . Speci cally, in case of COVID, studies from China 7 and Italy 8,9 have shown air pollution to be an important factor in disease transmission and mortality.…”
Section: Discussionmentioning
confidence: 99%